2022
DOI: 10.3390/ijms23169035
|View full text |Cite
|
Sign up to set email alerts
|

Alginate as a Promising Biopolymer in Drug Delivery and Wound Healing: A Review of the State-of-the-Art

Abstract: Biopolymeric nanoparticulate systems hold favorable carrier properties for active delivery. The enhancement in the research interest in alginate formulations in biomedical and pharmaceutical research, owing to its biodegradable, biocompatible, and bioadhesive characteristics, reiterates its future use as an efficient drug delivery matrix. Alginates, obtained from natural sources, are the colloidal polysaccharide group, which are water-soluble, non-toxic, and non-irritant. These are linear copolymeric blocks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 375 publications
1
46
0
Order By: Relevance
“…Alginate is one of the naturally abundant and anionic polysaccharides composed of the disaccharide repeating unit [GlcAβ (1)(2)(3)(4)Glcβ(1-3)], implying its low cost utilization. This anionic polymer is characteristic of biocompatibility, low toxicity, structural similarity to ECM and gelling capacity using different methods including covalent crosslinking, ionic crosslinking and thermal gelation (Abourehab et al, 2022). However, alginate hydrogels possess very weak mechanical properties, especially when they are hydrated in water, and have very low electrical and thermal conductivity, non-antibacterial activity, and very poor cell binding activity (Hurtado et al, 2022).…”
Section: Polysaccharide Materialsmentioning
confidence: 99%
“…Alginate is one of the naturally abundant and anionic polysaccharides composed of the disaccharide repeating unit [GlcAβ (1)(2)(3)(4)Glcβ(1-3)], implying its low cost utilization. This anionic polymer is characteristic of biocompatibility, low toxicity, structural similarity to ECM and gelling capacity using different methods including covalent crosslinking, ionic crosslinking and thermal gelation (Abourehab et al, 2022). However, alginate hydrogels possess very weak mechanical properties, especially when they are hydrated in water, and have very low electrical and thermal conductivity, non-antibacterial activity, and very poor cell binding activity (Hurtado et al, 2022).…”
Section: Polysaccharide Materialsmentioning
confidence: 99%
“…Catanzano et al [ 101 ] proposed polysaccharide hydrogels combining hyaluronan (HA) in a physically cross-linked alginate (ALG) for dermal wound repair that promoted wound closure after 5 days on a rat model of an excised wound. Abourehab et al [ 102 ] reported the attractive properties of alginate for wound care, such as biocompatibility and high-water absorption, minimizing bacterial contamination and wound secretions. HA also contribute to the management of wounds, regulating tissue hydrodynamics, cell migration and proliferation, and the remodeling and repair process of the extracellular matrix [ 103 ].…”
Section: Treatments For Topical Infected Woundsmentioning
confidence: 99%
“…There are numerous natural polymers that function as bone bio-based adhesives, mostly polymers consisted of animal-inspired bio-based adhesives, such as frog, sandcastle, mussel, polysaccharides, and fibrin glue [31][32][33][34][35][36][37][38]. The most broadly utilized material for soft tissue bio-based adhesives, sealants, and hemostatic agents is fibrin.…”
Section: Sources and Types Of Bio-based Adhesivesmentioning
confidence: 99%